Farmer Childrenâs Willingness for Dairy Farming succession in Banyumas Regency - Muatip, Krismiwati; Sugiarto, Moch (ANIMAL PRODUCTION, 2016)
The objectives of this research were to 1) observe the age, education, farm parentsâ cattle ownership, parentsâ income, childrenâs perception and willingness for farming succession, and 2) investigate the relationship between age, education, farm parentsâ cattle ownership, parentsâ income, childrenâs perception of and willingness for farming succession. Purposive sampling was used to determine the regional sample in three districts in Banyumas regency with the most dairy cow population and were the supervised area subject to âPesatâ Milk Cooperative. Ninety respondents from 10-30 years old were determined. Result showed that farmersâ children had better education than the parents with average age of 21,67 years old. Average cattle ownership was 1-15 heads per household with Rp 564.167 â Rp 4.523.333monthly income. Farmersâ children shaped positive perception on dairy farming and had willingness for farming succession. Age was positively correlated with farming perception and willingness of the farmersâ children, while education was negatively correlated.